Parametric optimisation of a combined supercritical CO2 (S-CO2) cycle and organic Rankine cycle (ORC) system for internal combustion engine (ICE) waste-heat recovery - Song,J; Li,X; Wang,K; Markides,CN (Energy Conversion and Management, 2020)
Supercritical CO2 (S-CO2) power-cycle systems are a promising technology for waste-heat recovery from internal combustion engines (ICEs). However, the effective utilisation of the heat from both the exhaust gases and cooling circuit by a standalone S-CO2 cycle system remains a challenge due to the unmatched thermal load of these heat sources, while a large amount of unexploited heat is directly rejected in the system’s pre-cooler. In this paper, a combined-cycle system for ICE waste-heat recovery is presented that couples an S-CO2 cycle to a bottoming organic Rankine cycle (ORC), which recovers heat rejected from the S-CO2 cycle system, as well as thermal energy available from the jacket-water and exhaust-gas streams that have not been utilised by the S-CO2 cycle system. Parametric optimisation is implemented to determine operating conditions for both cycles from thermodynamic and economic perspectives. With a baseline case using a standalone S-CO2 cycle system for an ICE with a rated power output of 1170 kW, our investigation reveals that the combined-cycle system can deliver a maximum net power output of 215 kW at a minimum specific investment cost (SIC) of 4670 $/kW, which are 58% and 4% higher than those of the standalone S-CO2 cycle system, respectively. A range of ICEs of different sizes are also considered, with significant performance improvements indicating a promising potential of exploiting such combined-cycle systems. This work motivates the pursuit of further performance improvements to waste-heat recovery systems from ICEs and other similar applications.